Factors Associated With Diagnostic Delays in Human Brucellosis in Tongliao City, Inner Mongolia Autonomous Region, China - Jingbo Zhai; Ruihao Peng; Ying Wang; Yuying Lu; Huaimin Yi; Jinling Liu; Jiahai Lu; Zeliang Chen; Zeliang Chen; Zeliang Chen; Zeliang Chen (Frontiers Media S.A., 2021)
The diagnostic delays pose a huge challenge to human brucellosis (HB), which increases the risk of chronicity and complications with a heavy disease burden. This study aimed to quantify and identify the associated factors in the diagnostic delays to its prevention, reduction, and elimination. This study analyzed risk factors associated with the diagnostic delays in a cross-sectional study with data collected from Tongliao City, Inner Mongolia Autonomous Region of China. Diagnostic delays were defined with a cutoff of 30, 60, and 90 days. In different delay groups, risk factors of diagnostic delays were analyzed by univariate analysis and modeled by multivariate logistic regression analysis. A total of 14,506 cases were collected between January 1, 2005, and December 31, 2017, of which the median diagnostic delays was 29 days [interquartile range (IQR): 14-54 days]. Logistic regression analysis indicated that the older age category was associated with longer diagnostic delays across all groups. Longer diagnostic delays increase with age among three delay groups (p for trend <0.001). Occupation as herdsman was associated with shorter diagnostic delays in group 1 with 30 days [adjusted odds ratio (aOR), 0.890 (95% CI 0.804-0.986)]. Diagnostic delays was shorter in patients with brucellosis who were reported in CDC in all delay groups [aOR 0.738 (95% CI 0.690-0.790), 0.539 (95% CI 0.497-0.586), and 0.559 (95% CI 0.504-0.621)]. Pastoral/agricultural area was associated with shorter diagnostic delays in group 1 with 30 days [aOR, 0.889 (95%CI 0.831-0.951)] and group 3 with 90 days [aOR, 0.806 (95%CI 0.727-0.893)]. Stratified analysis showed that the older age category was associated with an increased risk of a long delay in both genders (p < 0.05). The older age group-to-youth group OR increased along with increased delay time (p for trend <0.001). Furthermore, the pastoral/agricultural area was associated with a shorter delay in males (p < 0.05). Delays exist in the diagnosis of HB. We should pay great attention to the risk factors of diagnostic delays, such as older population, non-herdsman, non-pastoral/agricultural area, non-disease prevention, and control agencies. Effective measures should shorten the diagnostic delays, achieve early detection, diagnosis, and treatment, and reduce the risk of HB's chronicity, complications, and economic burden.